Framing the Emerging Talent Crisis in India and China: A Human Capital Perspective. (June 2014) - Chatterjee, Samir; Nankervis, Alan; Connell, Julia
China and India have undergone significant transformation in recent years as they emerge as the drivers of the so-called "Asian Century". Although the catalyst for this remarkable growth has been the ability of both countries to harness talent, the next two decades will require a very different dispersion of skills. India will increase its working age population by an additional 200 million, while the workforce in China will reduce by 100 million. In the next three decades, China will have more than doubled its population of those aged 65 and over resulting in a weaker dependency ratio. This article examines the multifaceted challenges that are emerging due to significant skills shortages in China and India. Through the lens of human capital theory, two new frameworks are introduced in order to analyze these factors and to suggest potential solutions.